Recent Advances in Grain Crops Research 2020
DOI: 10.5772/intechopen.86340
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological and Photosynthetic Reactions of Wheat (T. aestivum L.) and Its Wild Congeners to Drought Condition In Vivo and In Vitro

Abstract: The results of the complex analysis of different wheat species tolerance to drought stress in vivo at different levels of organization as well as in vitro on callus cultures, which was conducted, are presented. The objects of research are as follows: species of wheat-T. monococum L. (A u ), T. dicoccum Shuebl. (A u B), T. polonicum L. (A u B), T. aethiopicum Jakubz. (A u B), T. macha Dek.et.Men. (A u BD), T. compactum Host. (A u BD), and T. aestivum L. (A u BD). The methods of this research are physiological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A decrease in the size of the main conducting bundle during drought is directly related to a decrease in the size of the xylem region, which is directly responsible for the ability of plants to absorb water and conduct nutrients, changing the diameter of the vessel [21]. Drought-resistant forms of wheat under conditions of water and temperature stresses form a more powerful conducting system of leaves [8,[24][25][26]. Judging by the data presented, line D-d-05 in terms of the diameter of the central conducting bundle can also be considered the most droughtresistant of the presented forms.…”
Section: Results Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in the size of the main conducting bundle during drought is directly related to a decrease in the size of the xylem region, which is directly responsible for the ability of plants to absorb water and conduct nutrients, changing the diameter of the vessel [21]. Drought-resistant forms of wheat under conditions of water and temperature stresses form a more powerful conducting system of leaves [8,[24][25][26]. Judging by the data presented, line D-d-05 in terms of the diameter of the central conducting bundle can also be considered the most droughtresistant of the presented forms.…”
Section: Results Of Researchmentioning
confidence: 99%
“…An increase of the size of the flag leaf led to an increase of productivity due to an increase in the grain content of the ear, however, the grain size decreased [7]. Many studies including our previous research deal with changes of the photosynthetic apparatus of wheat in relation to an increased level of ploidy and the transition from wild to cultural forms and also with changes in the leaf anatomy [8], in the photochemical and photophosphorylating activity of photosynthetic pigments [9,10] as well as features of the anatomical organization of the wheat leaf [11]. It was shown that the structural features of the leaf at different phases of its development are of great importance for the formation of resistance to unfavorable factors -extreme temperatures and damages induced by diseases and pests.…”
Section: Introductionmentioning
confidence: 99%